1984
DOI: 10.1152/ajprenal.1984.246.6.f772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium intake on steady-state potassium excretion

Abstract: The effects of changes in sodium intake on the steady-state relationship between plasma potassium concentration and potassium excretion were studied in 15 chronically adrenalectomized dogs. Throughout the experiments the dogs received aldosterone at a rate of 50 micrograms/day and methylprednisolone at 1 mg/day. The relationship between plasma potassium and steady-state potassium excretion was obtained by changing potassium intake from 10 to 30 to 100 meq/day, each level being maintained for 7-10 days. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
5
9
0
Order By: Relevance
“…This negative finding is in agreement with previous findings by Young et al (1984) and Lohmeier et al (1999). This negative finding is in agreement with previous findings by Young et al (1984) and Lohmeier et al (1999).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This negative finding is in agreement with previous findings by Young et al (1984) and Lohmeier et al (1999). This negative finding is in agreement with previous findings by Young et al (1984) and Lohmeier et al (1999).…”
Section: Discussionsupporting
confidence: 94%
“…Similar data have been seen in a previous study in our laboratory (unpublished data), and in other studies (Boemke et al 1990, Young et al 1984, Hall et al 1980, DeClue et al 1978. In conscious dogs, Young et al (1984) found a 0.54 AE 0.20 mm decrease in plasma potassium concentration in response to increasing NaInt from 10 to 100 mEq day )1 ($0.6-5.6 mmol kg )1 day )1 ) on a fixed potassium intake of 30 mEq day )1 ($1.7 mmol kg )1 day )1 ). The corresponding plasma potassium concentrations were 3.93 AE 0.25 and 3.67 AE 0.37 mol L )1 , respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…38 Dietary potassium readily alters plasma potassium up to 4.2 mmol/L. 34 " 37 The ability of potassium intake to alter plasma potassium above 4.2 mmol/L is directly related to dietary sodium. 34 ] of Ham's F-12K with 10% FBS is 5.1 mmol/L, and that of RPMI 1640 with 10% FBS is 6.1 mmol/L.…”
Section: P Otassium Intake (60 To 80mentioning
confidence: 99%
“…34 " 37 The ability of potassium intake to alter plasma potassium above 4.2 mmol/L is directly related to dietary sodium. 34 ] of Ham's F-12K with 10% FBS is 5.1 mmol/L, and that of RPMI 1640 with 10% FBS is 6.1 mmol/L. Cells were plated onto six-well plates (Costar) at a density of 250 000 cells per well and grown for up to 14 days.…”
Section: P Otassium Intake (60 To 80mentioning
confidence: 99%